Air Quality Index pada Koridor Hijau Sungai Jawi Pontianak Ruas Gertak 1 dan 2 - Fibrianto, Jockie Zudhy; Hilmy, Mochamad; Maulana, Deni (Politeknik Negeri Pontianak, 2024)
The Air Quality Index (AQI) is a benchmark for the health of a city by measuring the levels of each air pollution parameter (Yiyi Wang, 2023). AQI in a city increases due to the high use of oil-fueled vehicles, increasing population, and minimal vegetation in an urban area. Green corridors in cities are part of green infrastructure which plays an important role in reducing air pollution. The green corridor of the Jawi River in Pontianak City is a green corridor which also contains a blue corridor, namely the Jawi River which is a tributary of the Kapuas River in Pontianak. Gertak 1 and gertak 2 are segmentations of the Jawi River green corridor which are the delineation of research, in identifying AQI and identifying the ability of vegetation to absorb CO2. By carrying out direct measurements and analyzing air quality levels according to the Air Pollution Standard Index (ISPU), the Air Pollutant Index (API) results were obtained, which then created an infographic map of air pollution in the Jawi River green corridor. This API measurement stage is a method in this research, which is part of the Environmental Quality Index (EQI) measurement component.